Controlling Single Molecule Conductance by a Locally Induced Chemical Reaction on Individual Thiophene Units - Michnowicz, Tomasz; Borca, Bogdana; Pétuya, Rémi; Schendel, Verena; Pristl, Marcel; Pentegov, Ivan; Kraft, Ulrike; Klauk, Hagen; Wahl, Peter; Mutombo, Pingo; Jelínek, Pavel; Arnau, Andrés; et al. (Angewandte Chemie (International ed. in English), 2020)
Among the prerequisites for the progress of single-molecule-based electronic devices are a better understanding of the electronic properties at the individual molecular level and the development of methods to tune the charge transport through molecular junctions. Scanning tunneling microscopy (STM) is an ideal tool not only for the characterization, but also for the manipulation of single atoms and molecules on surfaces. The conductance through a single molecule can be measured by contacting the molecule with atomic precision and forming a molecular bridge between the metallic STM tip electrode and the metallic surface electrode. The parameters affecting the conductance are mainly related to their electronic structure and to the coupling to the metallic electrodes. Here, the experimental and theoretical analyses are focused on single tetracenothiophene molecules and demonstrate that an in situ-induced direct desulfurization reaction of the thiophene moiety strongly improves the molecular anchoring by forming covalent bonds between molecular carbon and copper surface atoms. This bond formation leads to an increase of the conductance by about 50 % compared to the initial state.
Keywords: DFT; STM/AFM; strong anchoring; covalent-bond formation; single-molecule conductance